2017
DOI: 10.1186/s40068-017-0093-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of land resource management practices on erosion and vegetative cover using GIS and remote sensing techniques in Melaka watershed, Ethiopia

Abstract: Background: Land resource management measures, such as soil bund, trench, check dams and plantation had been practiced in Melaka watershed, Ethiopia since 2010. The objective of this study is to assess the impact of above measures on soil loss rate, vegetative cover and livelihood of the population. Results:The land cover spatial data sets were created from Landsat satellite images of 2010 and 2015 using ERDAS IMAGINE 2014 ® . Soil loss rate was calculated using Revised Universal Soil Loss Equation (RUSLE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Clearing the Earth's forests on a large scale worldwide (UNEP 2012;Marques et al 2016) and particularly in Ethiopia (Kassa et al 2016;Belay and Mengistu 2019) for pasture or crop cultivation is ensuing many land damages (Demissie et al 2017;Tolessa et al 2019). Clearing of the forest has happened in Ethiopia since the earliest time (Ariti et al 2015;Mekuriaw 2017), and even become more intense within the past 30 years in the name of investors (Alemu 2017; Ketema et al 2020). Unregulated commercial land resources exploitation by the investors is causing huge forest destruction, land degradation, and disruption of wildlife resources (Kassa et al 2016;Besada 2017).…”
Section: Land Use/land Cover Changes For Agriculturementioning
confidence: 99%
“…Clearing the Earth's forests on a large scale worldwide (UNEP 2012;Marques et al 2016) and particularly in Ethiopia (Kassa et al 2016;Belay and Mengistu 2019) for pasture or crop cultivation is ensuing many land damages (Demissie et al 2017;Tolessa et al 2019). Clearing of the forest has happened in Ethiopia since the earliest time (Ariti et al 2015;Mekuriaw 2017), and even become more intense within the past 30 years in the name of investors (Alemu 2017; Ketema et al 2020). Unregulated commercial land resources exploitation by the investors is causing huge forest destruction, land degradation, and disruption of wildlife resources (Kassa et al 2016;Besada 2017).…”
Section: Land Use/land Cover Changes For Agriculturementioning
confidence: 99%
“…On the other hand, there is no consent on the effectiveness of SWC interventions among the research findings reported so far (Dagnew et al 2015). Some argue that SWC contributes for reduction in runoff and sediment loss (Mekuriaw 2017) and increased soil moisture conservation (Haregeweyn et al 2015;Nyssen et al 2010). On the other side, it is reported that SWC structures were not effective in reducing soil erosion (Bewket and Sterk 2002) and had not resulted in decreasing sediment concentrations (Temesgen et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…But now-adays land resources are not used in a proper way and hence there is an imbalance. When land is utilised beyond its capability, it may results in the deterioration of land (Mekuriaw 2017). Therefore, proper utilisation of land and land resources to fulfil the requirements and increasing demand of growing population is very necessary.…”
Section: Introductionmentioning
confidence: 99%